The Land roads in the Bilad Al-Sham 1900 /1800 # 1215 / 1318 - البودي مازن (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The paper talks about the necessary linkage between people, the basic crossing points that must be followed daily, the compulsory transportation lines for the permanent movement of goods, and the paths that determine the movement of army units in terms of speed, safety, and ability to fight. The flow of goods and the degree of the state’s interest in them, in a way that serves its economic and social plans, in a way that reflects the state and its important geographical location.